Natural Histories, expeditions, global networks and Natural History Museums in Chile (XVIII-XX Centuries) - Valenzuela Matus, Carolina; Garrido, Francisco (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2023)
Natural History Museums in Chile have been the subject of historical interest because they were closely linked to the formation of the nation-state, and were protagonists of the configuration of a scientific culture in the country. Historical approach es have moved from a historical analysis of 19th century official ideals of «progress», to a new focus on the scientific influences of the 18th century and the importance of the exchanges and global networks of the 19th century, with a particular interest on the people who built those spaces. Therefore, in this paper we consider the temporal span from the enlightened 18th century to the beginning of the 20th century. This period was characterized by a scientific specialization that went beyond the taxonomic classification of nature, to focus on understanding the change and phylogenetic relationship among species as an evolutionary process.In this way, through a historiographical analysis we examine the construction of the history of the collections and the natural history museums, emphasizing in the networks of multiple social actors that contributed to their formation development and public knowledge.
Keywords: Natural History Museums; expeditions; natural histories; global networks; Chile